Histological Subtypes of Non-Hodgkin’s Lymphoma in Different Age and Sex Groups - Akhter, A; Rahman, MR; Majid, N; Shermin, S; Saleheen, MS; Rajib, RC; Ullah, SMA; Haque, N; Akond, AK (Bangladesh Medical Journal, 2014)
Non Hodgkin's lymphomas (NHL) constitute a heterogeneous group of neoplasm of the lymphoid system. There are many histological subtype of NHL based on WHO classification of haemotopoietic and lymphoid neoplasm. This cross-sectional study was carried out in the department of Pathology, Dhaka Medical College, Dhaka from January 2009 to December 2010 to observe the different subtypes of NHL in different age and sex groups. A total of 50 microscopically diagnosed case of NHL irrespective of age and sex were included in the study. The diagnostic morphologic criteria of each lymphoma subcategory were compiled and diagnoses were made. Mean age of the study subjects were 42.0±19.7 years with range 3-75 years and male female ratio was 1.8:1. Maximum number of histolgic subtypes belonged to diffuse large B-cell lymphoma (DLBCL) and male was predominant in all histological subtypes, except peripheral T-cell lymphoma (PTCL). The most childhood patients belonged to lymphoblastic lymphoma. Regarding cell lineage B-cell NHL case was more common than T-cell NHL (88% vs. 12%), but high grade pattern was more predominant in T-cell type (83.3% vs. 65.9%). DOI: http://dx.doi.org/10.3329/bmj.v41i1.18779 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 32-36